Hollow acanthosphere-shaped phosphorus-doped nine-cobalt octasulfide / foamed nickel electrode material and preparation method thereof
Through the preparation of hollow spherical phosphorus-doped Nine Cobalt Octa-Nine-Sulphide/foam nickel electrode material, the problem of insufficient conductivity and structural stability of transition metal sulfide electrode materials is solved, and the energy density and electrochemical performance of the supercapacitor are significantly improved.
Patent Information
- Application Number
- CN202411820320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing transition metal sulfide supercapacitor electrode materials have low electronic conductivity and poor structural stability, which limits their energy storage performance.
Hollow spherical phosphorus doped with octa-nine cobalt sulfide/foam nickel electrode material is used to improve the conductivity and structural stability of the material through the hydration-sulfide-phosphorus doping treatment method.
High conductivity, high structural stability and high specific surface area are achieved, which significantly improves the energy density and electrochemical properties of supercapacitors.
Smart Images

Figure CN119419074A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supercapacitor electrode material preparation, and particularly relates to a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material and a preparation method thereof. Background Art
[0002] Nowadays, energy shortage and environmental problems are becoming increasingly serious, and high-performance energy storage and conversion devices are urgently needed. Among the many storage and conversion devices, supercapacitors have excellent storage performance due to their unique electrochemical properties, such as fast charging and discharging, long cycle life, and environmental friendliness. However, the low energy storage performance of supercapacitors has always limited their commercial application. Current research has found that the energy storage of supercapacitors depends on the electrode material. Therefore, designing and constructing reasonable supercapacitor electrode materials is an effective way to improve their storage performance.
[0003] Transition metal sulfides (Co9S8, MoS2, etc.) have attracted widespread attention as supercapacitor electrode materials due to their high theoretical capacitance and abundant active sites. However, when used as supercapacitor electrode materials, transition metal sulfides have low electronic conductivity and poor structural stability. In order to improve the conductivity of transition metal sulfides, researchers have tried many methods, such as ion doping of transition metal sulfides and composite carbon-based materials to improve their conductivity. Among them, ion-doped (P, N, B, etc.) transition metal sulfides show high electronic conductivity. Using ion doping technology to improve the energy storage of transition metal sulfide electrode materials is an effective method. However, the poor structural stability of transition metal sulfides is still a key issue limiting the energy storage of supercapacitors.
[0004] The structure of the electrode material is a key factor affecting the energy storage of supercapacitors. Today, the structures of supercapacitor electrode materials include spheres, nanosheets, rods, etc. The hollow structure is considered to be a very promising electrode material structure because it can alleviate the volume and stress changes caused by electrochemical reactions. In addition, the hollow structure can also increase the contact area between the electrolyte and the electrode material, promote electron transfer during the electrochemical reaction, and facilitate the energy storage and conversion of supercapacitors. However, in practice, the use of hollow structures as supercapacitor electrode materials is limited by stacking and cannot give full play to the large specific surface area characteristics, which greatly weakens the energy storage in the electrochemical process. Therefore, for transition metal sulfide electrode materials, how to increase their surface area while improving electronic conductivity and ensuring their structural stability is a technical problem that needs to be solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material and a preparation method thereof, using nickel foam (NF) as a current collector and through a hydration-sulfurization-phosphorus doping method, a supercapacitor electrode material with high conductivity, high structural stability, high specific surface area and high energy density is prepared.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0008] Step 1: nickel foam pretreatment;
[0009] The nickel foam is cut, cleaned to remove impurities and dried to obtain a nickel foam substrate, referred to as NF;
[0010] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0011] After the cobalt salt, fluorine source and promoter are stirred and dissolved, they are transferred into a reactor to in-situ grow Co(OH)F on the nickel foam through a hydrothermal reaction. After the reaction is completed, the product is washed and dried to obtain a Co(OH)F-NF precursor.
[0012] Step 3: Sulfidation to prepare Co9S8-NF
[0013] Stir and dissolve the sulfur source, transfer it into the reactor, and add the Co(OH)F-NF precursor in step 2. After the sulfurization reaction, wash and dry to obtain Co9S8-NF;
[0014] Step 4: Preparation of P-Co9S8-NF by phosphorus doping
[0015] The Co9S8-NF in step 3 is co-calcined with a phosphorus source under inert gas protection to obtain P-Co9S8-NF.
[0016] Furthermore, the Co(OH)F-NF precursor has a thorny spherical structure, while Co9S8-NF and P-Co9S8-NF have a hollow thorny spherical structure.
[0017] Furthermore, in step 1, the nickel foam is cut into a disc shape, placed in acetone, anhydrous ethanol, and deionized water in sequence for ultrasonic cleaning, and placed in an oven for drying.
[0018] Furthermore, in step 2, the cobalt salt is Co(NO3)2·6H2O, the fluorine source is NH4F, the promoter is CH4N2O, and the mass ratio of Co(NO3)2·6H2O, NH4F and CH4N2O is (2-4):1:(2-4);
[0019] The hydrothermal reaction temperature in step 2 is 110° C.-130° C., and the reaction time is 6 h-9 h.
[0020] Furthermore, in step 3, the sulfur source is CH3CSNH2 or CH4N2S, and the solvent for dissolving the sulfur source is anhydrous ethanol or deionized water;
[0021] In the step 3, the sulfurization reaction temperature is 105° C.-135° C., and the reaction time is 4 h-12 h.
[0022] Further, in step 4, the phosphorus source is NaH2PO2·H2O or (NH4)2HPO4;
[0023] In the step 4, a tubular furnace is used for calcination, the heating rate is 2°C / min-5°C / min, the temperature is raised to 300°C-350°C, and the temperature is kept for 0.5h-1.5h.
[0024] The present invention also provides a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material, which is prepared by adopting the preparation method of the hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material.
[0025] The present invention provides application of a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material in a supercapacitor.
[0026] The application of the hollow thorn spherical phosphorus-doped cobalt octasulfide / nickel foam electrode material in supercapacitors adopts a three-electrode system for electrochemical performance testing, wherein the working electrode is P-Co9S8-NF material, the counter electrode is a platinum sheet, the reference electrode is a calomel electrode, and the electrolyte is KOH.
[0027] Furthermore, the electrolyte concentration is 1 mol / L-6 mol / L.
[0028] Advantages and effects of the present invention:
[0029] The hollow thorn spherical phosphorus-doped cobalt octasulfide / nickel foam electrode material prepared by the present invention can produce good application value and prospects in supercapacitor electrode materials. The present invention uses NF as a current collector and adopts a hydration-sulfurization-P doping method to prepare a hollow thorn spherical supercapacitor electrode material, wherein NF is used as a current collector, which is conducive to the dispersion of the electrode material and avoids the problem of low ion transmission efficiency caused by the accumulation of the electrode material; the synthesis method of P-Co9S8-NF is simple and easy to synthesize, and the hollow structure formed by P-Co9S8-NF can alleviate the volume and stress changes caused by electrochemical reactions, increase the contact area between the electrolyte and the electrode material, and improve the stability of the electrode material; the introduction of the P element improves the conductivity of the electrode material, which is conducive to the transmission of electrons, and the effective synergy of the P-Co9S8-NF structure can effectively improve the energy storage performance of the supercapacitor; the preparation process of this P-doped hollow thorn spherical Co9S8 supercapacitor electrode material is simple, easy to implement, and has a low preparation cost, which can lay a technical support for the preparation of supercapacitors with high conductivity, high structural stability, and high energy storage electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 1 are scanning electron microscope (SEM) images of Co(OH)F-NF, Co9S8-NF and P-Co9S8-NF materials prepared in Example 1, wherein a is a SEM image of Co(OH)F-NF, b is a SEM image of Co9S8-NF, c is a local magnified SEM image of P-Co9S8-NF, and d is a SEM image of P-Co9S8-NF;
[0031] Figure 2 is a transmission electron microscope (TEM) image of the P-Co9S8-NF material prepared in Example 1;
[0032] Figure 3 is the X-ray diffraction (XRD) pattern of Co9S8-NF and P-Co9S8-NF materials prepared in Example 1;
[0033] Figure 4 The cyclic voltammetry (CV) curves of Co9S8-NF and P-Co9S8-NF in Application Example 1 at a scan rate of 3 mV / s;
[0034] Figure 5 The Co9S8-NF and P-Co9S8-NF in Application Example 1 were tested at a current density of 3 mA / cm 2 Constant current charge and discharge (GCD) curve;
[0035] Figure 6 The cyclic voltammetry (CV) curves of P-Co9S8-NF in Application Example 1 at scan rates of 1 mV / s, 3 mV / s and 5 mV / s;
[0036] Figure 7 The P-Co9S8-NF electrode material in Application Example 1 is at a current density of 3 mA / cm 2 , 5mA / cm 2 and 10mA / cm 2 Constant current charge and discharge (GCD) curve under ;
[0037] Figure 8 is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 2;
[0038] Fig. 9 is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 3;
[0039] Fig.10 is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 4;
[0040] Fig.11 is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 5;
[0041] Fig.12 is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 6;
[0042] Fig.13 is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 7;
[0043] Fig.14 This is a scanning electron microscope (SEM) image of the P-Co9S8-NF material prepared in Example 8. DETAILED DESCRIPTION
[0044] The present invention is described in detail below with reference to the embodiments.
[0045] Example 1
[0046] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0047] Step 1: NF pretreatment
[0048] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0049] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0050] Co(NO3)2·6H2O (0.3 g), NH4F (0.15 g) and CH4N2O (0.30 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution was pink. The solution was poured into a 100 mL reactor, and the NF was placed at the bottom of the reactor. The reactor was placed in an oven at 120°C for 9 h for hydrothermal reaction. The reactor temperature was lowered to room temperature, the NF was taken out, washed several times with deionized water, and dried in an oven at 60°C for 6 h to obtain a precursor spherical Co(OH)F-NF precursor.
[0051] Step 3: Sulfidation to prepare Co9S8-NF
[0052] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 120°C for 8 hours, cool to room temperature, wash with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0053] Step 4: P-doping to prepare P-Co9S8-NF
[0054] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 300°C at a rate of 2°C / min and kept warm for 1 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0055] Example 2
[0056] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0057] Step 1: NF pretreatment
[0058] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0059] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0060] Co(NO3)2·6H2O (0.6 g), NH4F (0.15 g) and CH4N2O (0.6 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 130°C for 6 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0061] Step 3: Sulfidation to prepare Co9S8-NF
[0062] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 120°C for 8 hours, cool to room temperature, wash with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0063] Step 4: P-doping to prepare P-Co9S8-NF
[0064] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 300°C at a rate of 3°C / min and kept warm for 1.5 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0065] Example 3
[0066] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0067] Step 1: NF pretreatment
[0068] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0069] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0070] Co(NO3)2·6H2O (0.45 g), NH4F (0.15 g) and CH4N2O (0.45 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 125°C for 7 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0071] Step 3: Sulfidation to prepare Co9S8-NF
[0072] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 105°C for 12 hours, cool to room temperature, wash it with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0073] Step 4: P-doping to prepare P-Co9S8-NF
[0074] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 310°C at a rate of 2°C / min and kept warm for 1.3 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0075] Example 4
[0076] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0077] Step 1: NF pretreatment
[0078] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0079] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0080] Co(NO3)2·6H2O (0.3 g), NH4F (0.15 g) and CH4N2O (0.3 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 120°C for 8 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0081] Step 3: Sulfidation to prepare Co9S8-NF
[0082] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 110°C for 10 hours, cool to room temperature, wash with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0083] Step 4: P-doping to prepare P-Co9S8-NF
[0084] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 320°C at a rate of 4°C / min and kept warm for 1.1 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0085] Example 5
[0086] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0087] Step 1: NF pretreatment
[0088] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0089] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0090] Co(NO3)2·6H2O (0.3 g), NH4F (0.15 g) and CH4N2O (0.3 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 115°C for 9 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0091] Step 3: Sulfidation to prepare Co9S8-NF
[0092] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 115°C for 8 hours, cool to room temperature, wash with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0093] Step 4: P-doping to prepare P-Co9S8-NF
[0094] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 350°C at a rate of 5°C / min and kept warm for 0.5 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0095] Example 6
[0096] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0097] Step 1: NF pretreatment
[0098] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0099] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0100] Co(NO3)2·6H2O (0.3 g), NH4F (0.15 g) and CH4N2O (0.3 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 120°C for 9 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0101] Step 3: Sulfidation to prepare Co9S8-NF
[0102] Measure 30 mL of deionized water, dissolve CH4N2S (0.030 g) in deionized water at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 125°C for 6 hours, cool to room temperature, wash with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0103] Step 4: P-doping to prepare P-Co9S8-NF
[0104] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 330°C at a rate of 3°C / min and kept warm for 0.9 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0105] Example 7
[0106] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0107] Step 1: NF pretreatment
[0108] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0109] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0110] Co(NO3)2·6H2O (0.3 g), NH4F (0.15 g) and CH4N2O (0.3 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 110°C for 9 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0111] Step 3: Sulfidation to prepare Co9S8-NF
[0112] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 130°C for 5 hours, cool to room temperature, wash with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0113] Step 4: P-doping to prepare P-Co9S8-NF
[0114] Place (NH4)2HPO4 (0.02 g) and a piece of Co9S8-NF prepared in step 3 into a porcelain boat, place (NH4)2HPO4 upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, heat the temperature to 340°C at a rate of 4°C / min and keep warm for 0.7 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0115] Example 8
[0116] A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material comprises the following steps:
[0117] Step 1: NF pretreatment
[0118] The NFs were cut into 0.5 cm discs, placed in 20 mL of acetone, anhydrous ethanol, and deionized water, respectively, for ultrasonic treatment to remove impurities on the NF surface, and dried in an oven at 60 °C for 6 h.
[0119] Step 2: Preparation of Co(OH)F-NF precursor by hydration
[0120] Co(NO3)2·6H2O (0.3 g), NH4F (0.15 g) and CH4N2O (0.3 g) were dissolved in 20 mL of deionized water under stirring at room temperature. The solution turned pink. The solution was poured into a 100 mL reactor. The NF was placed at the bottom of the reactor and kept at 120°C for 9 h for hydrothermal reaction. The precursor was washed with deionized water several times and dried in an oven at 60°C for 6 h to obtain the precursor spherical Co(OH)F-NF precursor.
[0121] Step 3: Sulfidation to prepare Co9S8-NF
[0122] Measure 30 mL of anhydrous ethanol, dissolve CH3CSNH2 (0.030 g) in anhydrous ethanol at room temperature, and stir until dissolved; then, transfer the above solution into a 100 mL reactor, and then put the Co(OH)F-NF precursor prepared in step 2 into the reactor for sulfurization reaction, keep it in an oven at 135°C for 4 hours, cool to room temperature, wash it with anhydrous ethanol several times, and dry it in an oven at 60°C for 6 hours to obtain black hollow spherical Co9S8-NF.
[0123] Step 4: P-doping to prepare P-Co9S8-NF
[0124] NaH2PO2·H2O (0.02 g) and a piece of Co9S8-NF prepared in step 3 were placed in a porcelain boat. NaH2PO2·H2O was placed upstream of the tubular furnace (i.e., the direction in which Ar flows into the tubular furnace), and Co9S8-NF was located downstream (i.e., the direction in which Ar flows out of the tubular furnace). Under Ar protection, the temperature was raised to 350°C at a rate of 5°C / min and kept warm for 1 h to obtain the target product, hollow spherical P-Co9S8-NF.
[0125] Application Example 1
[0126] The P-Co9S8-NF prepared in the preparation method of Example 1 was used as an electrode material in a supercapacitor.
[0127] The electrochemical performance test adopted a three-electrode system, with the working electrode being P-Co9S8-NF material, the counter electrode being a platinum sheet, the reference electrode being a calomel electrode, and the electrolyte being a 6 mol / L KOH solution.
[0128] Characterization of properties
[0129] Figure 1 The figure shows the scanning electron microscope test results of Co(OH)F-NF, Co9S8-NF and P-Co9S8-NF materials prepared by the preparation method of Example 1 of the present invention, wherein: Figure 1 The a in the middle is Co(OH)F-NF with a spherical structure, which is about 15 μm in size and grows evenly; Figure 1Figure b is Co9S8-NF obtained after sulfurization treatment. The spherical structure remains intact and is not damaged by sulfurization treatment, indicating that the spherical structure has excellent stability. Figure 1 Figure c is a partial enlarged image of P-Co9S8-NF obtained after phosphorus doping treatment. It can be seen from the figure that P-Co9S8-NF is evenly dispersed on NF and grows stably without accumulation and phosphorus doping shedding, indicating that the material has excellent dispersibility and stability. Figure 1 Figure d is a scanning electron microscope image of P-Co9S8-NF. Compared with Figures a and b, P-Co9S8-NF still presents a thorny ball structure, its size has not changed, and there is no obvious microstructural change, which once again proves that the thorny ball structure has excellent structural stability.
[0130] Figure 2 Shown are the transmission electron microscopy test results of the P-Co9S8-NF material in the preparation method of a hollow thorny spherical phosphorus-doped cobalt octasulfide / nickel foam electrode material in Example 1 of the present invention. It can be seen from the figure that the P-Co9S8-NF material is a hollow structure with a wall thickness of about 3.60 nm. A good hollow structure can provide the material with a large specific surface area, can alleviate stress and volume changes during the electrochemical reaction, is beneficial to ion transmission, and lays the foundation for supercapacitors to achieve high energy storage.
[0131] Figure 3 Shown is the XRD spectrum of Co9S8-NF and P-Co9S8-NF materials in the preparation method of a hollow thorny spherical phosphorus-doped cobalt octasulfide / nickel foam electrode material in Example 1 of the present invention. It can be seen from the figure that the three peaks of 2θ at 44.49°, 51.84° and 76.37° are the characteristic peaks of NF; the characteristic peak of Co9S8 coincides with the characteristic peak of NF at 51.84°, and there is a characteristic peak of Co9S8 at 26.04°. Since the diffraction peak intensity of NF is strong, the diffraction peak intensity of Co9S8 is weak; after phosphorus doping, the diffraction peak of Co9S8 at 26.04° shifts to the negative direction, and the diffraction peak intensity decreases, indicating that phosphorus doping has a certain influence on the diffraction peak of Co9S8 and reduces its crystallinity. The above shows that Co9S8 is successfully prepared and the P element is successfully doped into the Co9S8 material.
[0132] Figure 4 Shown are the CV curves of Co9S8-NF and P-Co9S8-NF as electrode materials at a scan rate of 3 mV / s in Application Example 1 of the present invention; it can be seen from the figure that both of them have a pair of redox peaks as electrode materials, indicating that they have pseudocapacitive properties. In addition, the CV curve area of P-Co9S8-NF as an electrode material is significantly larger than that of Co9S8-NF, indicating that the storage performance of the electrode material is effectively improved after the addition of P element.
[0133] Figure 5 The figure shows the current density of Co9S8-NF and P-Co9S8-NF as electrode materials in Application Example 1 of the present invention at 3 mA / cm 2 GCD curves at 3 mA / cm2. As can be seen from the figure, the two electrode materials have a pair of charge and discharge platforms, which once again confirms that they have pseudocapacitive properties. In addition, P-Co9S8-NF shows a longer discharge time, indicating that the electrode material has better electrochemical performance. At a current density of 3 mA / cm2, 2 When the area capacitance of Co9S8-NF is 11.78F / cm 2 , while the area capacitance of P-Co9S8-NF reaches 15.47F / cm 2 , which shows that the doping of P element effectively improves the conductivity of the electrode material and promotes the energy storage of the electrode material.
[0134] Figure 6 Shown are the CV curves of the P-Co9S8-NF electrode material at scan rates of 1 mV / s, 3 mV / s and 5 mV / s in Application Example 1 of the present invention; as the scan rate increases, the CV curve area of the P-Co9S8-NF electrode material increases, but still shows a very obvious redox peak, indicating that the electrode material has good rate performance.
[0135] Figure 7 The figure shows the P-Co9S8-NF electrode material in Application Example 1 of the present invention at 3 mA / cm 2 , 5mA / cm 2 and 10mA / cm 2 GCD test results under current density; it can be found from the figure that the electrode material is 2 The redox peaks of P-Co9S8-NF are still very obvious when the current density is 3 mA / cm 2 , 5mA / cm 2 and 10mA / cm 2 When the area capacitance is 15.47F / cm 2 、15.06F / cm 2 and 14.65F / cm 2 , even at a high current density of 10mA / cm 2 Under these conditions, P-Co9S8-NF can still exhibit good capacitance performance, indicating that the electrode material has very good energy storage properties.
[0136] Figure 8-Figure 14The results shown are scanning electron microscope test results of the P-Co9S8-NF materials prepared in Examples 2-8 of the present invention, and all show a spiky ball structure.
Claims
1. A method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material, characterized in that: The following steps are involved: Step 1: nickel foam pretreatment; The nickel foam is cut, cleaned to remove impurities and dried to obtain a nickel foam substrate, referred to as NF; Step 2: Preparation of Co(OH)F-NF precursor by hydration After the cobalt salt, fluorine source and promoter are stirred and dissolved, they are transferred into a reactor to in-situ grow Co(OH)F on the nickel foam through a hydrothermal reaction. After the reaction is completed, the product is washed and dried to obtain a Co(OH)F-NF precursor. Step 3: Sulfidation to prepare Co9S8-NF Stir and dissolve the sulfur source, transfer it into the reactor, and add the Co(OH)F-NF precursor in step 2. After the sulfurization reaction, wash and dry to obtain Co9S8-NF; Step 4: Preparation of P-Co9S8-NF by phosphorus doping The Co9S8-NF in step 3 is co-calcined with a phosphorus source under inert gas protection to obtain P-Co9S8-NF.
2. The method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material according to claim 1, characterized in that: The Co(OH)F-NF precursor has a thorny ball structure, while Co9S8-NF and P-Co9S8-NF have a hollow thorny ball structure.
3. The method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material according to claim 1, characterized in that: In the step 1, the nickel foam is cut into a disc shape, placed in acetone, anhydrous ethanol, and deionized water in sequence for ultrasonic cleaning, and placed in an oven for drying.
4. The method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material according to claim 1, characterized in that: In step 2, the cobalt salt is Co(NO3)2·6H2O, the fluorine source is NH4F, the promoter is CH4N2O, and the mass ratio of Co(NO3)2·6H2O, NH4F and CH4N2O is (2-4):1:(2-4); the hydrothermal reaction temperature is 110℃-130℃, and the reaction time is 6h-9h.
5. The method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material according to claim 1, characterized in that: In step 3, the sulfur source is CH3CSNH2 or CH4N2S, and the solvent for dissolving the sulfur source is anhydrous ethanol or deionized water; the sulfurization reaction temperature is 105°C-135°C, and the reaction time is 4h-12h.
6. The method for preparing a hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material according to claim 1, characterized in that: In step 4, the phosphorus source is NaH2PO2·H2O or (NH 4)2 HPO4; use a tubular furnace for calcination, with a heating rate of 2°C / min-5°C / min, heating to 300°C-350°C, and keeping warm for 0.5h-1.5h.
7. A hollow thorn spherical phosphorus-doped cobalt octasulfide / nickel foam electrode material, characterized in that: The hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material is prepared using the preparation method described in any one of claims 1 to 6.
8. Use of the hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material as described in claim 7 in a supercapacitor.
9. The use of the hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material in a supercapacitor according to claim 8, characterized in that: The electrochemical performance test adopted a three-electrode system, with the working electrode being P-Co9S8-NF material, the counter electrode being a platinum sheet, the reference electrode being a calomel electrode, and the electrolyte being KOH.
10. The use of the hollow thorn spherical phosphorus-doped nonacobalt octasulfide / nickel foam electrode material in a supercapacitor according to claim 9, characterized in that: The electrolyte concentration is 1 mol / L-6 mol / L.
Citation Information
Patent Citations
Yttrium-phosphorus co-doped Co(OH)F supported on nickel foam, preparation method and applications thereof
CN110354875A
Surface sulfur-doped cobalt phosphide nanomaterial and preparation method thereof
CN110745801A
Preparation method and application of P-doped FeS / Co3S4 / Co9S8 composite material
CN113380552A
Preparation method of high-performance nano sea urchin structure electrode material
CN114360919A
Hollow Co9S8 composite material derived from ZIF-67 grown on rod-like radiation cluster CoO in situ and preparation method of hollow Co9S8 composite material
CN116564720A